As concepções de estudantes do ensino fundamental de escolas públicas de Santa Maria-RS sobre alimentação - Righi, Márcia Medianeira Toniasso (2010)
Education is understood as a process of human development. Linked to this process, there is the food, that is also essential and important. Thus, it is important that all citizens have access to quality food to be healthy as well. To have a healthy diet, we must take into account the amount and variety of food needed daily for proper functioning of our body. Thus this study investigated the conceptions of elementary school students about food, being held in 2008 and 2009 with students from 2nd to 9th grade in public schools of Santa Maria-RS. The instrument used for data collection was a questionnaire consisting of four open questions was applied in the Initial and Final Years of elementary school. It is perceived that participating students have prior knowledge in relation to food regardless of the year. These conceptions, even with the acquisition of new knowledge, remained the same since that show resistance to change. Regarding the importance of food, it is clear that students know that food is important for health and for their growth. With regard to what happens to food after it is ingested, they know that food goes to the stomach, but when questioned in relation to digestion, some ignore the subject, even if the content has been worked in the classroom. In relation to healthy eating in the early years they know that vegetables are important to health, and this knowledge it may have been acquired both in school and in family life or through media. In the final years, for students, the fruits are important, but few vegetables were cited. This is alarming, since they are essential items in order to have a healthy diet. There is a need for broadening the discussion on the topic in the food science curriculum in order to help teachers to develop new activities in the classroom, and also contribute significantly to the change of eating habits of students. It is also believed that the inclusion of activities related to food in the school environment since the early grades, through demonstration lessons, or even discussing ideas that appear in TV programs about diet and thus, together with students, able to produce materials such as comic books, primers that can be used by students so that they serve as multipliers of good eating habits in their community. Therefore, it is expected to contribute a significant learning effectively, through a reflection on the students' previous conceptions, which are important tools for the proposition teaching in the classroom.